Applying Cryo-X-ray Photoelectron Spectroscopy to Study the Surface Chemical Composition of Fungi and Viruses - Shchukarev, Andrey; Backman, Emelie; Watts, Samuel; Salentinig, Stefan; Urban, Constantin F.; Ramstedt, Madeleine (Frontiers in Chemistry, 2021)
Interaction between microorganisms and their surroundings are generally mediated via the cell wall or cell envelope. An understanding of the overall chemical composition of these surface layers may give clues on how these interactions occur and suggest mechanisms to manipulate them. This knowledge is key, for instance, in research aiming to reduce colonization of medical devices and device-related infections from different types of microorganisms. In this context, X-ray photoelectron spectroscopy (XPS) is a powerful technique as its analysis depth below 10 nm enables studies of the outermost surface structures of microorganism. Of specific interest for the study of biological systems is cryogenic XPS (cryo-XPS). This technique allows studies of intact fast-frozen hydrated samples without the need for pre-treatment procedures that may cause the cell structure to collapse or change due to the loss of water. Previously, cryo-XPS has been applied to study bacterial and algal surfaces with respect to their composition of lipids, polysaccharides and peptide (protein and/or peptidoglycan). This contribution focuses onto two other groups of microorganisms with widely different architecture and modes of life, namely fungi and viruses. It evaluates to what extent existing models for data treatment of XPS spectra can be applied to understand the chemical composition of their very different surface layers. XPS data from model organisms as well as reference substances representing specific building blocks of their surface were collected and are presented. These results aims to guide future analysis of the surface chemical composition of biological systems.